Graph usage in annual reports, evidence from Norwegian listed companies - Guddal, Tina (2016)
As investors and other users of annual reports often focus their attention on graphs, it is important that they portray accurate and reliable information. However, previous studies show that graphs often distort information and mislead users. This study analyses graph usage in annual reports from the 52 most traded Norwegian companies. The findings suggest that Norwegian companies commonly use graphs, and that the graph distortions, presentational enhancement and measurement distortion, are present. No evidence of selectivity was found. This study recommends development of guidelines for graphical disclosure, and advises preparers and users of annual reports to be aware of misleading graphs.